(3CMGOjK hCNHGQ ESdGejIs
(3ChdgG (B:s
(3eLdS ai PcQ HbjI NHQ YGO hbUI TOjO hTOGO hUfYI CQe PGJ GdYeGO s
(3BNQgG (B:s
(3eLdS ai bUI Be Ydjg GdSdGe hhLhg GdMceI hbGd HYV GdMceGA jG GHf BOe GfXQ Edi NWQ ebGec ai GdOfjG Ef QHc Ndb EHdjS hbGd aHYRJc dCZhjfge CLeYjf hCfJ GdeScjf hGddg CYde hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs